Pelatihan Pembuatan Lilin Aromaterapi Kulit Kopi Berbasis Minyak Jelantah Di Desa Mukai Pintu Kabupaten Kerinci - Edwin Permana; Nelson Nelson; Martina Asti Rahayu; Daniel Arsa; Khairul Alim; Dhian Eka Wijaya; Ali Nurdin Hidayat; Ardian Salsa Rusmana (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The abundance of waste cooking oil resulting from the cooking process has not yet been optimized for use. Apart from that, coffee is also produced in Mukai Pintu village, Kerinci Regency. The skin of these coffee beans is just waste that is thrown away. These two ingredients can be used to make aromatherapy candles which are useful for the community. In this way, the problem of waste coffee bean shells and used cooking oil can be overcome and become added value. Making aromatherapy candles from used cooking oil can be made easily by PKK women and the Mukai Pintu Kerinci village community. Coffee skin therapy aroma candles can support the economy of the community and village. Apart from that, this aromatherapy candle product made from coffee bean shells can be one of the superior products of the village and can be a souvenir from Kerinci Regency. The target for implementing this community service program is that partners are able to: 1) The community can apply and make aromatherapy candles from coffee bean shells. 2) can help the community improve the economy and can become a superior product for the village. 3) People can sell these products using digital marketing